The Influence of Good Corporate Governance, CEO Tenure, and Corporate Financial Performance on Company Value - Putra, I Gusti Made Priyambhada; Sunitha Devi (Universitas Pendidikan Ganesha, 2023)
Firm value is very important in an organization because it is related to the welfare of investors. The higher the company value causes the company to have a superior image and the value of the resources claimed by the company can be an impression of the company's value. But in society, there are phenomena and tendencies of individual behavior in choosing to invest. This study aims to determine the effect of good corporate governance, CEO tenure, and company financial performance on firm value. This type of research is quantitative research. This study uses secondary data from the Indonesia Stock Exchange. The population in this study are transportation sector companies listed on the Indonesia Stock Exchange in 2016-2020, totaling 8 companies. The sampling technique uses a side purposive technique. The dependent variable in this study is firm value as measured by Tobins'q. The independent variables in this study are good corporate governance which is proxied by the audit committee, company secretary, and remuneration committee, CEO tenure, and the company's financial performance which is proxied by ROA. The results of this study indicate that (1) the corporate secretary affects firm value; (2) the audit committee affects firm value; (3) the remuneration committee has an effect on firm value; (4) CEO tenure has an influence on firm value; and (5) ROA affects company value in various industrial sub-sectors listed on the IDX in 2016-2020. The results of this study expect that investors should always pay attention to internal and external elements in organizational valuation, namely the earth, social and financial benefits, which these three things must be balanced.